‘Bride Terrorist’ in Indonesia: Is She Still Considered as a Peace Agency? - Mia Dayanti Fajar; Elisabeth Dewi (Salasika, 2019)
ISIS and Al-Qaeda are now recruiting women to join terrorism groups. These two large terrorist groups even show the real use of women as suicide bombers in terrorist acts. This is certainly controversial since women have a close relationship with peace. It indicates a shift in traditional feminist thinking saying that women are identical with peace. The involvement of women in terrorism can also be traced in Indonesia. In December 2016, Indonesia was shocked by the arrest of a prospective suicide bomber with her husband. The phenomenon occurred along with female Chechen suicide bombers, Black Widows, who blew themselves up to avenge their husbands’ death. This paper aims to explain the involvement of women in the world of terrorism and any reason taken by women to commit suicide bombings. The result of this research revealed that women were involved in terrorism because of patriarchal culture and personal factors that was based on religion by doctrinization in Indonesia.